Analisis faktor-faktor yang mempengaruhi produksi patung kayu di kecamatan Tegalalang kabupaten Gianyar - Prastika, Tessa; Sutrisna, I Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2015)
thought to develop industry in the district gianyar statue, is a strategic effort in order to increase employment and income, reduce poverty especially Gianyar regency. Purpose of research determine the effect of capital, labor and technology simultaneously and partially on the production value of wood sculpture in District Tegalalang Gianyar regency. Research studies conducted in Village Terrace Tegalalang District of Gianyar Bali with multiple linear regression analysis using a sample of 62 business units. the results of the analysis concluded that capital, labor and technology simultaneously and partially significant effect on the value of production of wooden sculptures. Technology is the most variable production value in District Tegalalang wood sculpture with a value of 0.563. Keywords: production, capital, labor and technology.